2020
DOI: 10.1002/admi.202001051
|View full text |Cite
|
Sign up to set email alerts
|

Highly Mobile Levitating Soft Actuator Driven by Multistimuli‐Responses

Abstract: Soft actuators exhibit activeness and flexibility and are widely used as next‐generation intelligent devices. However, their locomotion depends on friction with contact surfaces that restrict their movement. To overcome this limitation, a noncontact‐type multiresponsive soft actuator that levitates in a magnetic field is proposed. This soft actuator can respond to humidity, heat, and diamagnetic repulsion force stimuli, resulting in high degrees of freedom and multiple motions. The soft actuator is fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To demonstrate the full versatility of the structures, we combine the optical and the magnetic actuation (Figure ). Notably, dual opto-magnetic soft actuators, where the mechanical structure can be actuated by both light and magnetic fields, are very scarce. , Although other actuators using light and magnetic fields can be found in the literature, the role of the magnetic field is merely to transport or rotate the structures, rather than for mechanical actuation. ,,, Since the magnetic actuation can drive the structure in both directions and the actuation mechanisms do not interfere between each other, we explore two different configurations by positioning the magnet to either (i) sum the optical and magnetic forces (Figure A, Video S1) or (ii) to counteract the optical actuation by magnetic forces and vice versa (Figure B, Video S2). In the first approach, the addition of photothermal and magnetic forces is shown in real time by the structure color red-shifting.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the full versatility of the structures, we combine the optical and the magnetic actuation (Figure ). Notably, dual opto-magnetic soft actuators, where the mechanical structure can be actuated by both light and magnetic fields, are very scarce. , Although other actuators using light and magnetic fields can be found in the literature, the role of the magnetic field is merely to transport or rotate the structures, rather than for mechanical actuation. ,,, Since the magnetic actuation can drive the structure in both directions and the actuation mechanisms do not interfere between each other, we explore two different configurations by positioning the magnet to either (i) sum the optical and magnetic forces (Figure A, Video S1) or (ii) to counteract the optical actuation by magnetic forces and vice versa (Figure B, Video S2). In the first approach, the addition of photothermal and magnetic forces is shown in real time by the structure color red-shifting.…”
Section: Resultsmentioning
confidence: 99%
“…The hard magnetic material used was a polymer composite made of magnetically hard ceramic ferrite powder implanted in a commercial epoxy resin [447]. Following this, there have been several studies that reported the usage of hMSMs in soft actuators [448][449][450][451]. For instance, Moreno-Mateos et al [452] have studied the effects of combining both hard and soft magnetic particles into the MRE, thereby making it a hybrid MRE for soft magnetic actuators.…”
Section: Magnetic Actuatorsmentioning
confidence: 99%
“…For decades, smart materials and systems whose shape, appearance, and physical performances can be changed autonomously in response to environmental stimuli have experienced a booming growth, and demonstrated fascinating prospects as actuators, including bionic prosthesis, soft robotics, smart apparatus, and so forth. [1][2][3] Various actuating materials, such as shape memory polymers, [4,5] carbon-based materials, [6][7][8] liquid-crystal elastomers, [9,10] and magnetic composite materials, [11,12] have been devoted to improve the deformation amplitude, response speed, and robust stability of soft actuators. In addition to efficient shape-change behavior, the feedback of deformation in real-time is also essential for the realization of smart actuators that can be automatically controlled by carbon-based actuators generally require high infrared intensity or temperature to be triggered due to the relative low infrared absorption or low thermal conductivity of functional material, such as rGO [21,24] and graphene.…”
Section: Introductionmentioning
confidence: 99%